The Impact of Off-Balance Sheet Items on Business Leadership: Case of Bank’s Technical Efficiency - Faouzi Saifi; Brahim Khouiled (Business Ethics and Leadership)
The study aims to determine the impact of off-balance sheet items on business leadership, focusing on the case of technical efficiency in 12 private banks operating in Algeria between 2011 and 2020. Technical efficiency (the dependent variable) was measured using the Data Envelopment Analysis (DEA) method by applying the variable return to scale model with input orientation (BCC-I) based on deposits and general exploitation expenditures as inputs and loans and net profit as outputs. As for the Off-Balance Sheet Items (the independent variable), they were expressed by the ratio of the total off-balance sheet financing to total assets, with the help of a set of control variables that reflect the bank's performance level. To measure the impact, panel data models were used. The study concluded that the business leadership in the private banks under investigation does not optimize their resources and that the off-balance sheet items significantly negatively impact these banks’ technical efficiency. This is attributed to the unregulated expansion of activities and operations related to off-balance sheet items by the business leadership in some banks, which has had negative effects on performance due to high costs.